PENGGUNAAN QUIZIZZ SEBAGAI PENDUKUNG MEDIA PEMBELAJARAN IPAS YANG MENARIK DI SEKOLAH DASAR - Mirna Astuti; Nor Hapipah; Farahah Kamilatun Nuha; Suci Skar Kinanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Technological developments include the world of education. Learning is also attempted to involve the presence of technology in the process. In the midst of technological advances, teachers are still found teaching in the old way which can be said to be monotonous without involving technology or media in the learning process. Whereas current technological developments allow teachers to utilize technology in learning. One of the technological media that teachers can utilize is smartphones by using quizizz media to create fun learning. This research was conducted to find out how to use quizizz media in the learning process so that it can create fun learning. . Supporting factors for the use of quizizz at Nadhlatul Ulama Elementary School Palangka Raya are the availability of school facilities to carry out this quizizz on learning in the form of a computer. The inhibiting factor in the use of quizizz is the lack of students' personal facilities to support the learning process including the procurement of smartphones, apart from that there are. The advantage of using the quizizz application is that it makes it easier for teachers and students in the learning process, teachers easily explain the material and students easily understand and are interested in learning. The drawback is that if you continue to use online-based learning, it will be difficult for students to control offline learning because students will continue to demand online learning, so it will be difficult for students to control offline learning.